STIGMASTANE-STEROID FROM THE BARK OF Chisocheton lasiocarfus (Meliaceae) - Nurlelasari, Nurlelasari; Abdullah, Fajar Fauzi; Thufaila, Nadya; Maharani, Rani; Harnet, Desi; Hidayat, Ace Tatang; Supratman, Unang (Jurnal Kimia (Journal of Chemistry), 2017)
Stigmastan-steroid, stigma-4-ene-3-on ( 1 ) has been isolated from the bark of Chisocheton lansiocarpus . The chemical structure of stigmastan-steroid was identified based on spectroscopic data and by comparison of spectral data obtained previously. The discovery of stigma-4-ene-3-on in C. lansiocarpus was shown in this study for the first time.